#### Answer

-10

#### Work Step by Step

Given -$x^{2}$ - 6 , x = -2
Now Put x = -2 in the given expression
= -$(-2)^{2}$ - 6
=-4-6
=-10

Published by
Pearson

ISBN 10:
0321867327

ISBN 13:
978-0-32186-732-2

-10

Given -$x^{2}$ - 6 , x = -2
Now Put x = -2 in the given expression
= -$(-2)^{2}$ - 6
=-4-6
=-10

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.